2010
DOI: 10.1007/s00122-010-1475-6
|View full text |Cite
|
Sign up to set email alerts
|

Variation of GmIRCHS (Glycine max inverted-repeat CHS pseudogene) is related to tolerance of low temperature-induced seed coat discoloration in yellow soybean

Abstract: In yellow soybean, seed coat pigmentation is inhibited by post-transcriptional gene silencing (PTGS) of chalcone synthase (CHS) genes. A CHS cluster named GmIRCHS (Glycine max inverted-repeat CHS pseudogene) is suggested to cause PTGS in yellow-hilum cultivars. Cold-induced seed coat discoloration (CD), a commercially serious deterioration of seed appearance, is caused by an inhibition of this PTGS upon exposure to low temperatures. In the highly CD-tolerant cultivar Toyoharuka, the GmIRCHS structure differs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…Among them, gSCC1 and gSCC8 corresponding to the two SCC genes, G (Song et al, 2004) and I (Ohnishi et al, 2011), respectively, were mapped into two small regions of 52,279,678–52,646,512 and 8,346,892–8,643,359 bp in NJRINP and 52,032,052–52,462,360 and 8,434,875–8,540,484 bp in NJRI4P on Chr. 01 and Chr.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, gSCC1 and gSCC8 corresponding to the two SCC genes, G (Song et al, 2004) and I (Ohnishi et al, 2011), respectively, were mapped into two small regions of 52,279,678–52,646,512 and 8,346,892–8,643,359 bp in NJRINP and 52,032,052–52,462,360 and 8,434,875–8,540,484 bp in NJRI4P on Chr. 01 and Chr.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the reference genome Wm82, the orders of most bins in each linkage map of NJRINP and NJRI4P showed good linear agreement with their physical positions. Using the two inter-specific maps, seven well-studied loci, B1 for SB (Chen and Shoemaker, 1998), G (Song et al, 2004) and I (Ohnishi et al, 2011) for SCC, and E2 (Watanabe et al, 2011), E3 (Watanabe et al, 2009), qDTF16.1 (Pooprompan et al, 2006) and two linked FLOWERING LOCUS T (Kong et al, 2010) for DTF, were detected, indicating the high quality of the two maps. The mapping accuracy was effectively improved, and few genes were contained in the 1-LOD interval of genes/QTLs.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, a DNA marker has been sought to aid breeding of highly CD-tolerant cultivars. A quantitative trait locus (QTL) analysis suggested that GmASCHS , or another gene tightly linked to it, may be responsible for CD tolerance, and a DNA marker discriminating between GmIRCHS and GmASCHS can be useful for marker-assisted selection of CD-tolerant plants (Ohnishi et al 2011). However, variation of GmIRCHS genotypes cannot necessarily explain all CD phenotypes, suggesting the existence of other QTLs for CD tolerance.…”
Section: Full and Partial Seed Coat Pigmentation In Yellow Soybeanmentioning
confidence: 99%
“…However, variation of GmIRCHS genotypes cannot necessarily explain all CD phenotypes, suggesting the existence of other QTLs for CD tolerance. Indeed, a second QTL has been identified, which made a smaller contribution to CD tolerance than GmIRCHS (Ohnishi et al 2011). If other QTLs are detected and mapped precisely, more reliable marker-assisted selection of CD tolerance could be achieved by the combination of DNA markers for GmIRCHS and other QTLs.…”
Section: Full and Partial Seed Coat Pigmentation In Yellow Soybeanmentioning
confidence: 99%
“…Chilling temperatures can also negatively affect seed appearance; for example, by causing seed coat discoloration and concomitant seed coat cracking (Funatsuki and Ohnishi 2009, Morrison et al 1998, Srinivasan and Arihara 1994, Takahashi and Abe 1994, 1999). A selection method for breeding soybeans tolerant to seed coat discoloration has been developed (Yumoto and Sasaki 1991), and the mechanism underlying seed coat discoloration has been clarified (Kasai et al 2009, Ohnishi et al 2011, Senda et al 2013). …”
Section: Introductionmentioning
confidence: 99%